How to hide an empire a history of the greater United States - Immerwahr, Daniel 1980- (New York Farrar, Straus and Giroux, 2019)
"A history of the United States' overseas possessions, from Puerto Rico to the Philippines and beyond, and what they reveal about the true meaning of American empire."--Provided by publisher.
Includes bibliographical references and index.
AIT-2192g donated by Prof. Ivan S. Henares.
Keywords: United States -- Territories and possessions -- History; United States -- Colonial question